Call for a European collaboration in the use of Real World Data in Health Technology Assessment. (13th November 2019) - Daugbjerg, S; Marchetti, M
Abstract: Issue/problem: Modern patient care requires a heavy investment in innovative health technologies while at the same time it is facing a fiscal sustainability challenge in the health care system. Evidence on effectiveness of health technologies informing Health Technology Assessments (HTA) have traditionally been based on randomized control trials (RCTs). However, RCTs are expensive and the external validity is relatively low which makes it difficult to assess effectiveness and long-term outcomes in clinical practice especially in diverse populations. Description of the problem: Real-World Data (RWD) studies use observational data routinely collected to gather information on the delivery and outcome of care. RWD studies cost less than RCTs and are considered to have a high external validity. Results from RWD studies are therefore a good supplement to support evidence from RCT in HTA-reports. However, RWD are not still fully used in HTA. This is partially due to concerns about data quality and accessibility. Effects/changes: In order to provide a deeper insight into how health technologies are working in real-world settings across Europe, it is time to systematically including RWD in HTA. A first step should be to call for a European collaboration to map relevant sources of RWD that can be used in HTA and define the quality and main format, in which they can be analysed and used. Common legislations and guidelines regarding which RWD should be accepted as sources of information for HTA should be elaborated. Lessons: Through a European collaboration, the quality and accessibility of RWD should be secured in order to use evidence from RWD studies to inform HTA on effectiveness of health technologies.